A descriptive study of dental treatments and services offered in San Fernando, Pampanga - Aum, Soun -lin
Many dentists prefer to work in the NCR but there are some who set up their practice in their provinces. The study aims to determine the availability of dental treatments and services in a semi-urban area using San Fernando as a sample town. 42 out of 68 private practicing dentists were chosen by simple random sampling method answered a questionnaire on treatment services and availability of dental materials and laboratories in San Fernando. The dentist-to-population ratio was calculated at 1:2,484. Results showed that 100% of the surveyed dentists offer complete denture service, 95% offer Periodotnal treatment and extraction, 92.9% offer Restorative treatment. Among the respondents, around 35% practice Orthodontics. 88% of the respondents avail of laboratory services in San Fernando. 90% said that basic dental materials are available in the area. All basic dental treatments are readily available to the population and Orthodontic treatment is the most common specialization in the area.